Languages Exchanges, Borrowings - Cukani, Fjona; Elezi, Gladiola (Mediterranean Journal of Social Sciences, 2012)
Linguistic communication was born as a necessity of human beings to communicate and to agree with one-other.According to Eduard Sapir, languages, like cultures, often turn out to be not self-sufficient systems – that is why the necessity foreconomic, commercial and political exchanges makes is obligatorily for human beings to communicate with each-other. Suchcommunication brings out linguistic interferences, which are expressed through linguistic loans from one language to another,and causes partial changes of the language that embrace these loans. It is evident that thanks to bilingual speakers, thelinguistic contacts and the linguistics loans happen. The linguistic contacts may happen in more various situations, in family, as itis the case of exogamy (a social arrangement where marriage is allowed only outside of a social/ethnic group), with theneighbours, at work etc. and may be of various intensity. In the majority of the cases, these contacts happen as a product ofindividual or group’s confrontation in a communicative discourse where various languages meet. Nowadays, Albanian languageis under the influence of foreign languages, English in particular and above all Italian and Greek – because of a considerablenumber of Albanians who have immigrated to Italy and Greece. There have been taken a lot of borrowings that do not exist inthe Albanian linguistic bedrock and there is a tendency that others will be borrowed more and more. Many denominations fromcomputational science, finance, market economy, modern arts etc, that have done remarkable progress, come into Albanianalong with the concepts they express filling up gaps of the lexicon. Loan words and calques may be grouped into specificsemantic fields where they appear more frequently